Humanitarian Law: Private Military Companies and Emerging Jurisprudential Issues - Miebaka Nabiebu; Michael Takim Otu; Amarachukwu Onyinyechi Ijiomah (Universitas Negeri Makassar, 2023)
The private military industry emerged in the initial years of the twentieth century, driven by three factors: the end of the Cold War; transformations in the nature of warfare that blurred the lines between soldiers and civilians; and a general trend towards privatisation and outsourcing of government functions worldwide. The dominance of State authority over the military is now under stress, and the professional and private elements—in the form of private military companies (PMCs)—are gaining ground. As the PMSCs become omnipotent and omnipresent, it becomes more difficult to hold the State accountable for its military activities. To further complicate the issue, the present international humanitarian law (IHL) does not consider PMCs as soldiers or supporting militias since they are not part of the defence force and often consist of a large number of people of different nationalities. Due to the above, this paper investigates Private Military companies and emerging Jurisprudential issues under international humanitarian law. This work discussed the emergence of private military companies, mercenaries, and combatants as war prisoners and the human rights violations perpetrated by PMSC personnel. This work used the US-based Black Water, CACI, L-3 Services, and DynCorp, the South African Meteoric Tactical Systems, as well as the Russian Wagner Group contractors, as case studies. This work also draws some lessons from the Iraq, Afghanistan, Somalia, And Ukraine conflicts. This work shows that Human rights violations perpetrated by PMSC personnel are rampant and often violate international humanitarian law. This work proposes that framers of international humanitarian laws should propose laws that will regulate the use of PMCs in conflict situations.